A round table discussion on forensic science in Australia - Houck, M.; Robertson, J.; Found, B.; Kobus, H.; Lewis, Simon; Raymond, M.; Reedy, P.; Ross, A.; Roux, C.; Vining, R. (Taylor and Francis, 2011)
This manuscript is an edited transcript of a round table discussion held during the Australian New Zealand Forensic Science Society International Symposium held in Sydney in 2010. The discussants covered a variety of topics, including the management of science, the handling of quality issues, and the report on forensic science from the U.S. National Academies of Science National Research Council. This discussion offers a frank account of the current state of Australian forensic service providers. These views are then considered in the context of recent events unfolding in the United Kingdom and in a broader international context. It poses the question, are there lessons to be learned from the Australian experience that would have relevance to other parts of the world?